Self-perceived health-related factors in Deaf Community in East Java, Indonesia - Astiarani, Yunisa; Putri, Giovani Indah Giantoro; Fitriah, Nur (Oto Rhino Laryngologica Indonesiana, 2023)
Background: Little is known about the perceived health of the Indonesian Deaf despite the rapid growth of the Deaf community and social organizations. Objective: The study aimed to investigate self-perceived health and related determinants among deaf adults in a Deaf community in East Java, Indonesia. Method: A survey study was conducted on 102 community members. Perceived health was assessed using a question: ‘In a scale of 1 to 10, how much will you give to rate your health?’. After stepwise suggestion and collinearity analysis, the association of demographic and health conditions was analyzed using logistic regression.Result: A High perceived health scale was reported from 77% of the members. Low perceived health was mainly stated by individuals from the 25–45 age, female, married, and working groups. Although most had no health complaints in the last month, 60% were hospitalized in the previous year. Lower educational levels, owned health insurance, frequently consuming vegetables, and fruits, and never being hospitalized were associated (p<0.05) with higher self-perceived health. Conclusion: Despite the high self-perceived health reported from most Deaf community members, the overall self-reported health conditions of Deaf community members are still a concern due to the high rate of hospitalization and lack of objective health assessment.